Comparative Analysis of Tax System Effectiveness in Developed and Developing Countries - Mohammad Ridwan Rumasukun; Muhammad Yamin Noch (Manunggal Halim Jaya, 2023)
This research delves into the comparative analysis of tax system effectiveness in developed and developing countries, aiming to provide valuable insights into the dynamics, challenges, and opportunities inherent in tax policy and administration across different contexts. Employing a qualitative approach, the study conducts a systematic review and analysis of relevant literature on tax system effectiveness, drawing from academic databases, journals, books, and government reports. The research identifies key dimensions of tax system effectiveness, including revenue adequacy, administrative efficiency, equity, simplicity, and transparency, and examines how these dimensions manifest differently in developed and developing countries. The analysis highlights disparities between developed and developing countries in achieving optimal performance across these dimensions, attributed to factors such as institutional frameworks, technological advancement, and economic structures. Additionally, the research investigates determinants of tax compliance behavior, emphasizing the role of tax morale, enforcement strategies, and social norms in influencing taxpayer compliance across different contexts. The study underscores the importance of context-specific approaches to addressing compliance challenges and achieving desired policy objectives. Furthermore, the research explores the comparative effectiveness of tax instruments, focusing on progressive income taxation and consumption taxes, and examines reform trajectories and policy implications based on tax reform experiences in select developing countries. Overall, the study contributes to a deeper understanding of tax system effectiveness and informs evidence-based policymaking and practice in both developed and developing countries.